Solidarity Across Cultures: Working Together For Democracy - Anwar Ibrahim (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
At the heart of the matter in diversity, the balancing of minority interests with the majority requires ingenuous commitment from both sides as represented by their respective community leaders. Religious strife of whatever denomination or faith would seriously undermine the very foundation of constitutional democracy. There is therefore much sense in the saying that the empowerment of one cultural group at the expense of another in any society would only lead to a clash of interests. This clash if left unchecked would threaten the essential overlapping consensus, recogni- zed as a central feature of the kind of democracy that we are talking about.